Shari’ah court and the role of muftīs in the Nigerian Judiciary: mission on reviving the lost glory of its past - Chiroma, Magaji; Arifin, Mahamad; Ansari, Abdul Haseeb; Abdullah, Mohamad Asmadi (UPM Press, 2015)
ABSTRACT Islamic institutions including courts and fatwā have been in existence in Nigeria since the advent of Islam in the country. While the courts were established in order to adjudicate between disputant parties, muftīs were also used as assessors (court officials) responsible for assisting the courts in dispensation of justice. When the colonial administrators came, they introduced their legal system to the colonies, which led to a gradual wipe away of some aspects of the Islamic legal system (including the courts and fatwā institutions). The doctrine of the tripartite tests (i.e., the repugnancy test, incompatibility test and public policy test) was introduced into the country’s legal system to the extent that the full and hitherto application of Islamic law was modified and some were suspended. Muslims are left with only matters related to civil causes and personal matters. Islamic jurists such as muftīs become functus officio in the Shari’ah Courts. In view of this, the paper explores the possibility of finding an avenue on how to revive the past glory of muftīs in the Nigerian judicial system. Thus, it sets out some modalities on how fatwā can be streamlined to achieving this objective. One of such modalities is to institutionalise fatwā in the country. Keywords: Shari’ah Court, role of a muftī, Nigeria, judiciary